Heartless : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2010)
After high school juniors Spencer, Emily, Hanna, and Aria think they have seen Ali, their missing and presumed dead friend, they pursue clues from a mysterious stalker, trying to find out if she is still alive.
Keywords: Friendship -- Juvenile fiction; Secrets -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Mystery fiction